Remembering to execute deferred tasks in simulated air traffic control: The impact of interruptions - Wilson, Micah; Farrell, S.; Visse, T.; Loft, S. (2018)
Air traffic controllers can sometimes forget to complete deferred tasks, with safety implications. In two experiments, we examined how the presence and type of interruptions influenced the probability and speed at which individuals remembered to perform deferred tasks in simulated air traffic control (ATC). Participants were required to accept/handoff aircraft, detect aircraft conflicts, and perform two deferred tasks: a deferred conflict task that required remembering to resolve a conflict in the future and a deferred handoff task that required substituting an alternative aircraft handoff action in place of routine handoff action. Relative to no interruption, a blank display interruption slowed deferred conflict resumption, but this effect was not augmented by a cognitively demanding n-back task or a secondary ATC task interruption. However, the ATC task interruption increased the probability of failing to resume the deferred conflict relative to the blank interruption. An ex-Gaussian model of resumption times revealed that these resumption failures likely reflected true forgetting of the deferred task. Deferred handoff task performance was unaffected by interruptions. These findings suggest that remembering to resume a deferred task in simulated ATC depended on frequent interaction with situational cues on the display and that individuals were particularly susceptible to interference-based forgetting.